Analysis Of Employee Competency in CV. Kampung Kaos Kidung, Prajegan Village, Sukorejo Subdistrict, Ponorogo in Islamic Perspective - Nurma Fitrianna; Titis Indrawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Every company needs competent employees to achieve the company's goals, vision, and mission. Competence in Islam is the feasibility of employees in carrying out their obligations (jobs). To measure the Competence of employees using three dimensions, namely knowledge, skills, and abilities. The Competence of these employees can increase along with the achievement of the company's vision and mission and the goals of the company, one of which is through training. The main purpose of this study was to analyze the Competence of employees with CV. Kampung Kaos Kidung in an Islamic perspective and efforts to improve the Competence of employees CV. Kampung Kaos Kidung. The type of research used in this research is field research with a research approach using a qualitative approach. This research was conducted on the CV Kampung Kaos Kidung with observation, interviews, and documentation data collection techniques. The results showed that the Competence of employees in the Islamic perspective was not good employees of CV. Because of poor Competence, Kampung Kaos Kidung has not carried out its job obligations. CV. Kampung Kaos Kidung has improved employee competence by training using two methods, namely information presentation and the job training method.